حفلات الطلاق : دراسة فقهية اجتماعية - عرب، عبدالعزيز بن سعود بن محمد (سليمان بن ابراهيم العايد, 2014)
مع تقادم الزمان وتأخره طرأت على الأسرة عوامل كثيرة سببت لها التفكك والتنافر بين الزوجين، فكثرت حالات الطلاق والشقاق، مما أدى إلى آثار سلبية في جوانب متعددة، حيث إن الأمر لم يقتصر على هذا بل تطور إلى ان رافقها في بعض البلدان والمناطق ما يسمى في عرف اليوم: (حفلات الطلاق)، حيث تقام لها المناسبات وتقدم فيها الدعوات، ولها أعراف ومظاهر ورسوم خاصة، وبدأ الحديث عنها في بعض المجالس ووسائل الإعلام، ووردت الأسئلة والاستفسارات على المفتين في حكم إقامتها والعمل بها. فكان لزاماً على أهل العلم وطلابه التفاعل مع مستجدات العصر ومشكلاته ومواكبة التطورات المجتمعية والحياتية، والمساهمة في تقديم النظرة والحلول الشرعية على وفق أصول النظر والاستدلال، فجاءت هذه الدراسة والتي هي بعنوان: (حفلات الطلاق – دراسة فقهية اجتماعية). Since ancient times until today, many factors that cause disintegration and disharmony between spouses have their impacts on the family. There are many cases of divorce and separation which have negative effects in many aspects. It is not stopped here, but in many places what it is called these days divorce parties have appeared. In such occasions people are invited and they have particular customs and norms. The divorce parties have been debated and argued in meetings and on media as well as many scholars have been asked about their opinions regarding their righteously. Therefore, it is necessary that people of knowledge interact with the contemporary issues in relation to the developments of social life. They also have to contribute to present the perspective of law based on wisdom and evidence principles. Thus, the present study titled The Divorce Parties: A Jurisprudence and Social Study fills such gap.
Keywords: الشريعة الإسلامية -- مقاصد الشريعة -- الأحكام الشرعية -- الفقه الإسلامي -- حفلات الطلاق